Exploring the audiological management of young children (0-6 years) diagnosed with bacterial meningitis - Tromp, Nikki (Division of Communication Sciences and Disorders, 2022)
Background. Internationally, infectious diseases remain the greatest cause of morbidity among young children. Infectious disease burden is particularly high in low-to-mid income countries (LMIC). South Africa has a high prevalence of bacterial meningitis (BM), especially in children under the age of five. BM is also one of the commonest causes of acquired hearing loss in children. Given the fluctuating and transient nature of BM-related hearing loss, there is a need for an effective audiological protocol to facilitate timeous and appropriate audiological management. There is currently no universally accepted protocol for the audiological referral and management of children diagnosed with BM. Consequently, there is a need for an evidence-based protocol that will ensure timely referral and audiological testing of all children diagnosed with BM. Early identification of BM-related hearing loss in children will allow for timeous, appropriate audiological management and associated benefits, such as an option for placement in mainstream schooling. Objectives. This study aimed to explore the audiological management of children diagnosed with BM at a tertiary hospital in the Western Cape, South Africa, with reference to: patterns of referral for audiological assessment following a diagnosis of BM; current audiological protocols for the management of children diagnosed with BM. It was anticipated that this study would generate evidence that could potentially be used to develop appropriate protocols for the audiological management of children diagnosed with BM in LMICs, specifically South Africa. Methods. A retrospective record review was conducted using patient folders of children between 0 and 6 years who were treated for BM between May 2016 and May 2018. Data collection took place at Red Cross War Memorial Children's Hospital, which has a paediatric infectious diseases unit and an audiology department. Demographic and audiological data were recorded on a self-developed data abstraction form and data were analysed descriptively. Results. A total of 291 patient folders were accessed for review in this study. Of those, 40 (13.7%) met the inclusion criteria for the study and were selected for review. The majority of excluded folders were for patients not referred for audiological testing post-BM diagnosis. For those children referred to audiology, average referral time was 15 days (SD = 24 days) and each patient attended an average of only 2 audiology appointments. Otoacoustic emissions testing and tympanometry were the most commonly performed audiological tests in all children. BM-related hearing loss developed in 2/19 of these patients. All patients who were diagnosed with BM-related hearing loss were subsequently fitted with hearing aids – one of whom was fitted unilaterally with a hearing aid and the other, a cochlear implant candidate, was lost to follow-up. Conclusions. The key challenge experienced in this study was low referral rates to audiology (16%), which was followed by poor adherence to follow-up appointments – both of which were found to impede effective audiological management. Effective management and prevention of BM-related hearing loss pose challenges in LMICs. This study highlights the need for a well-defined referral pathway and an evidence-based protocol for the audiological management of children with BM within the South African health care setting. If this could be achieved, the early identification of hearing loss in these children has the potential to provide them with developmental, scholastic, and working opportunities in line with those of children with normal hearing.